Pengaruh Strategi Pemasaran Terhadap Nilai Konsumen Yang Dimediasi Oleh Inovasi Produk : Studi Empiris Pada Pengerajin Kain Rang-Rang di Desa Pejukutan Kecamatan Nusa Penida - Asrida, Putu Diah; Firmani, Putu Siti; Amelis, Ni Wayan Sri Pitria; Pitaloka, Ni Kadek Putri Diah; Cahyani, Dewa Ayu Oka (Universitas Pendidikan Ganesha, 2022)
The increasingly fierce business competition makes the company always improve the synergies that exist within the company, namely the use of appropriate marketing strategies in accordance with the development of products and services produced by the company. Marketing programs can be designed using several programs simultaneously, including promotions, sales, personal selling, as well as company product development with the hope that the products and services produced by the company meet consumer needs and desires that can be increased to consumer value. This study was conducted to determine the effect of marketing strategy on consumer value mediated by product innovation (empirical study on rang-rang fabric craftsmen in the village of Pejukutan, sub-district of Nusa Penida). The method used by the sample in this study is non-probability sampling, with a sample size of 96. The data analysis technique used is the t-test with the Moderated Regression Analysis interaction test. This test has met the requirements of the instrument test, classical assumption test and the appropriate model test. Based on the test results, it is known that marketing strategy has a significant effect on consumer value with a regression coefficient of 0.840 with a significance of 0.000 <0.05 and a marketing strategy moderated by product innovation has a significant effect on consumer value with a regression coefficient value of -0.017 and a significance of 0.007 <0.05 Therefore, product innovation variable is able to moderate the influence of marketing strategy on consumer value